WORLDVIEW DAN SIKAP TERHADAP KEBIJAKAN PUBLIK - Vinaya Vinaya (MANASA, 2012)
This research examined the relationship between six dimensions of worldview and attitude on public policies related to the renewal of Islamic thought. Characteristic of the respondent is Moslem and minimum have been graduated from high school. Worldview Assessment Instrument (Koliko-Rivera, 2000) and attitude on public policies related to the renewal of Islamic thought scale was used on 453 respondents. The result show that five dimensions of worldview (‘agency’, metaphysic, ‘relation to group’, ‘mutability’, and ‘relation to authority’) significantly correlated with attitude on public policies related to renewal of Islamic thought.